Kritik Nalar Ushul Fiqh: Telaah Komentar Ibnu Rushd Atas Ushul Fiqh al-Ghazali - Aksin Wijaya (Justicia Islamica, 2008)
This study aims to examine Ibn Rushd's criticism of al-Ghazali's usul fiqh reasoning, especially in the aspects of methodology and rationality of Islamic law. Ibn Rushd, as a philosopher and faqih, tried to balance philosophical reasoning and shar'i rules in responding to al-Ghazali's approach, which was considered too theocentric and Sufi. This study uses a qualitative method with a literature study approach, analyzing the main works of both figures such as al-Mustashfa and Bidayat al-Mujtahid. The results show that Ibn Rushd criticized the tendency towards subjectivity in the istihsan and maqashid methods used by al-Ghazali, and emphasized the importance of a rational approach and logical consistency in the istinbath of law. This study shows the intellectual dynamics in classical usul al-fiqh, as well as Ibn Rushd's contribution to strengthening the framework of Islamic legal rationality.